La apertura a la realidad (LS 114), ¿un remedio a las deformaciones del paradigma tecnocrático? (2024)
This article presents the epistemological dimensions of the term "technocratic paradigm" which is used by Francis in Laudato Si' and Laudate Deum to describe our relationship with technology, and through it, with Creation; the Pope considers this attitude as the human roots of the ecological crisis. The article begins expounding the very concept of technocratic paradigm as it is presented by the Pontiff in the above-mentioned documents; it has been frequently gone under the radar of most of the comments written about the encyclical. The article underlines its cognoscitive dimensions because it argues that those are de origin of the disordering of the relationship between humankind and the environment. The article presents also technology as a form of knowledge, to show more clearly the epistemological biases embedded in the technocratic paradigm and, at the same time, shows how the Pope's position is very close to some of the current philosophical and theological analysis of technology. Finally, it will show the ways to overcome these biases, as proposed by Francis, in order to build a sound relationship with technology that can lead us to care about our Common Home, as the Pontiff and contemporary environmentalist in general, aspire.